wiiw - POLMIG database: An inventory of migration policy changes in Europe, 2013-2019 - Isilda Mara; Sandra Kovacevic (The Vienna Institute for International Economic Studies (wiiw), 2021)
The following work has been conducted with the aim of providing detailed information on migration policy changes implemented in Europe between 2013 and 2019. It examines new measures, laws and regulations grouped by policy area, target group and typology of policy change. It provides detailed, categorized and sub-categorized changes in migration policies, including both immigration and emigration policies. The following database offers numerous possibilities for further investigation and indepth analyses of migration policy changes in a systematic way across time and EU countries.
Keywords: 330; migration; immigration; emigration; database; Europe; policy change